Relationship between ACE gene polymorphism and ischemic chronic heart failure in Turkish population - (:unkn) unknown (I HOLZAPFEL VERLAG GMBH, 2003)
Background: Angiotensin-converting enzyme (ACE) gene insertion/deletion (I/D) polymorphism has been associated with the development of left ventricular hypertrophy, myocardial infarction, and remodeling. However, little is known about its role in ischemic chronic heart failure (CHF). We investigated the relationship between ACE gene I/D polymorphism and ischemic CHF and its influence on exercise capacity. Methods: ACE gene I/D polymorphisin was analyzed in 209 Turkish patients with coronary artery disease (CAD) undergoing coronary angiography. ACE genotype distributions were examined in 84 consecutive patients with ischemic CHF, functional capacity class II-IV to New York Heart Association and left ventricular ejection fraction (LVEF) < 40% and 125 consecutive patients with stable angina pectoris and LVEF greater than or equal to 40%. Furthermore the results of the cardiopulmonary exercise testing (CPX) in each ACE genotype were compared in medically treated ischemic CHF patients (n = 84). Results: ACE genotype distributions were similar between the patients with and without symptomatic CHF in CAD. The odds ratios were 0.95 for D homozygotes (p > 0.05) and 0.98 for the D allele (p > 0.05). In patients with ischemic CHF the differences in CPX findings were statistically not significant in ACE D/D, I/D and I/I genotypes (peak oxygen consumptions 13.7 +/- 4.6; 14.6 +/- 5.1 and 14.5 +/- 5.0 ml/kg/min, respectively (p > 0.05). Conclusions: In this study population, there was no evidence that ACE gene I/D polymorphism plays a role in the development of CHF in CAD or any influence on exercise capacity in treated patients with ischemic CHF.
Keywords: heart failure; coronary artery disease; ACE gene; exercise capacity; ANGIOTENSIN-CONVERTING-ENZYME; CORONARY-ARTERY DISEASE; LEFT-VENTRICULAR HYPERTROPHY; MYOCARDIAL-INFARCTION; INSERTION/DELETION POLYMORPHISM; DELETION POLYMORPHISM; EXERCISE CAPACITY; CLINICAL CHARACTERISTICS; DILATED CARDIOMYOPATHY; DD-GENOTYPE